Depressive Symptoms and Short Telomere Length Are Associated with Increased Mortality in Bladder Cancer Patients - Lin, Jie (Cancer Epidemiol Biomarkers Prev, 2014)
BACKGROUND: Depression is associated with an increased risk of mortality in cancer patients; it has been hypothesized that depression-associated alterations in cell aging mechanisms in particular, the telomere/telomerase maintenance system, may underlie this increased risk. We evaluated the association of depressive symptoms and telomere length to mortality and recurrence/progression in 464 bladder cancer patients. METHODS: We used the CES-D and SCID to assess current depressive symptoms and lifetime MDD, respectively, and telomere length was assessed from peripheral blood lymphocytes. Multivariate Cox regression was used to assess the association of depression, and telomere length to outcomes and the joint effect of both. Kaplan-Meier plots and log rank tests were used to compare survival time of subgroups by depression variables and telomere length. RESULTS: Patients with depressive symptoms (CES-D ≥16) had a 1.83-fold (95%CI= 1.08 to 3.08, P=0.024) increased risk of mortality compared to patients without depressive symptoms (CES-D < 16) and shorter disease-free survival time (P=0.004). Patients with both depressive symptoms and lifetime history of MDD were at 4.88-fold (95%CI=1.40 to 16.99; P=0.013) increased risk compared to patients with neither condition. Compared to patients without depressive symptoms and long telomere length, patients with depressive symptoms and short telomeres exhibited a 4-fold increased risk of mortality (HR=3.96, 95% CI=1.86 to 8.41, P=0.0003) and significantly shorter disease-free survival time (P<0.001). CONCLUSION: Short telomere length and depressive symptoms are associated with bladder cancer mortality individually and jointly. IMPACT: Further investigation of interventions that impact depression and telomere length may be warranted in cancer patients.